House lessons : renovating a life - Bauermeister, Erica (Sasquatch Books, 2020)
"In this memoir-in-essays, New York Times bestselling author Erica Bauermeister renovates a trash-filled house in the eccentric town of Port Townsend, WA, and in the process takes readers on a journey into the ways our spaces subliminally affect us, ultimately showing us how to make our houses (and lives) better"--